2015
DOI: 10.4049/jimmunol.1500767
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Antigen to Clec9A Primes Follicular Th Cell Memory Responses Capable of Robust Recall

Abstract: Targeting Ags to dendritic cell (DC) surface receptors can induce a variety of responses depending on the DC type targeted, the receptor targeted, and the adjuvant used. Clec9A (DNGR-1), which is expressed by CD8+ DCs, has been shown to bind F-actin exposed on damaged cells. Targeting Ag to this receptor in mice and nonhuman primates induces strong humoral immunity even in the absence of adjuvant, a process seen for a few select DC receptors. In contrast with other receptors, however, targeting Clec9A induces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 61 publications
3
60
0
Order By: Relevance
“…This agrees with existing literature showing that the CD8 + DC subset preferentially generates Th1 responses over Th2 responses (35,36) and is efficient at promoting Tfh cell immunity (73,74). The consequences of this functional capacity for CD8 + DC, however, are likely to differ depending on the model studied, resulting in the induction of pathology or immunity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This agrees with existing literature showing that the CD8 + DC subset preferentially generates Th1 responses over Th2 responses (35,36) and is efficient at promoting Tfh cell immunity (73,74). The consequences of this functional capacity for CD8 + DC, however, are likely to differ depending on the model studied, resulting in the induction of pathology or immunity.…”
Section: Discussionsupporting
confidence: 90%
“…DC subsets can influence the expression of transcription factors by T cells and drive their differentiation into particular Th phenotypes (35,36,(73)(74)(75). To address the role of CD8 + DC on the differentiation of PbT-II cells after PbA infection, XCR1-DTRvenus mice were adoptively transferred with PbT-II cells and then infected with 10 4 PbA iRBC.…”
Section: Cd8 + DC Influence Th1 and Follicular Th Cell Inductionmentioning
confidence: 99%
“…The location of monocytes within the interfollicular region suggests that they may directly or indirectly contribute to B cell maturation and/or antibody production. Indeed, an elegant study by Chakarov and Fazilleau 128,129 demonstrated that, similarly to cDCs [130][131][132][133][134][135][136] , Toll-like receptor 9 (TLR9)-stimulated monocytes directly present antigen and induce the differentiation of T FH cells via IL-6 production. Another study using a high-dose antigen regimen suggested that in the absence of cDCs, LY6C + monocytes (along with B cells) induce T FH cell development 137 .…”
Section: Antigen-presenting Monocytes Induce T Fh Cellsmentioning
confidence: 99%
“…Their use has been extensively investigated for enhancing antigen presentation, but their ability to trigger CLR signalling has been only marginally investigated. A few soluble antibodies are known to induce CLR signalling: the CLEC9A-trageting antibody 24/04-10B4 has been shown to induce T FH cell responses 97 , and the polyclonal DC-SIGN-targeting antibody H-200 triggers signalling similar to that of mannose ligands 111 . The high specificity of antibodies underscores their possible application in triggering CLRs.…”
Section: Harnessing Clrs For Vaccine Designmentioning
confidence: 99%
“…Therefore, vaccines that induce efficient T FH cell responses might elicit these broadly neutralizing anti bodies. Interestingly, in contrast to other PRRs, some CLRs, such as DC-SIGN and CLEC9A, have been shown to specifically elicit T FH cell responses 11,97 . Thus, CLR targeting might also present an important opportunity to induce strong antibody responses against HIV-1.…”
Section: Harnessing Clrs For Vaccine Designmentioning
confidence: 99%